Probiotics, prebiotics, and synbiotics for patients with autism spectrum disorder: a meta-analysis and umbrella review - Rahim, Fakher; Toguzbaeva, Karlygash; Qasim, Nameer Hashim; Dzhusupov, Kenesh O.; Zhumagaliuly, Abzal; Khozhamkul, Rabiga (Frontiers in Nutrition, 2023)
The potential impact of gut health on general physical and mental well-being, particularly in relation to brain function, has led to a growing interest in the potential health advantages of prebiotics, probiotics, and synbiotics for the management of ASD.The present study employed a comprehensive examination of various electronic databases yielded a total of 3,393 records that were deemed possibly pertinent to the study. RCTs encompassed a total of 720 individuals between the ages of 2 and 17, as well as 112 adults and participants ranging from 5 to 55 years old, all of whom had received a diagnosis of ASD. Overall, 10 studies reported Autism-Related Behavioral Symptoms (ARBS). Regarding the enhancement of autism-related behavioral symptoms, there wasn't a substantial variation between the treatment groups statistically(combined standardized mean difference = -0.07, 95% confidence interval: -0.39 to 0.24, Z = 0.46, p = 0.65). We found that the beta band frontopolar power significantly decreased from baseline to endpoints in patients with ASD who were given probiotics. (Baseline: 13.09 ± 3.46, vs. endpoint: 10.75 ± 2.42, p = 0.043, respectively) and gamma band (Baseline: 5.80 ± 2.42, vs. endpoint: 4.63 ± 1.39, p = 0.033, respectively). Frontopolar gamma-band coherence was significantly correlated (negatively) with all biochemical measures tested and TNF-α (r = -0.30, p = 0.04). In conclusion, the existing body of research provides a comprehensive analysis of the developing evidence that indicates the potential of probiotics, prebiotics, and synbiotics as therapeutic therapies for ASD. Our findings revealed that those there was no significant effect of such therapy on autism-related behavioral symptoms, it has significant effect on the brain connectivity through frontopolar power in beta and gamma bands mediated by chemicals and cytokines, such as TNF-α. The psychobiotics showed no serious side-effects.